正交面齿轮功率分流传动系统非线性动力学研究 - 高红英 (Jixie chuandong)
The bend-torsional coupling nonlinear dynamics model of power split transmissions of face gear is established.The time-varying mesh stiffness,mesh phase,meshing error and tooth backlash are included in the model.Based on the numerical solutions,the dynamic load factor and the phase diagram,Poincare map,FFT diagram of the dynamic response are analyzed.The results show that the dynamic load level of each path is different,and quasi-periodic responses,chaos responses can be obtained at different revolving speeds.Then,the dynamic load factor and the phase diagram of the dynamic response are analyzed for different tooth backlash,the results show that the dynamic characteristic will not change with the variation of tooth backlash when the value of tooth backlash is greater than a certain critical value.